Diseño de un manual para la correcta implementación de las 9´S en las empresas de fabricación de postes de hormigón de la ciudad de Latacunga. - Lema Través, Edwin Manuel (2020)
The present study is established in the benefits that are obtained from the principles of the 9's methodology; for which it has been called the design of a manual for the correct implementation of the 9s', in the companies that manufacture concrete posts in the city of Latacunga; which has the purpose of inquiring about the literature of studies related to the 9's methodology to know the operations and modes of application of each of the principles of this study; with the help of a documentary bibliographical research. Subsequently, the current situation of the production process of these companies was determined; Next, and with the help of the collected data, it was possible to establish the methodological procedures in the design of a manual for the correct implementation of this methodology, according to the needs and deficiencies identified in the companies that manufacture concrete poles. the city of Latacunga